ANALISIS PUTUSAN HAKIM TERHADAP TINDAK PIDANA PENADAHAN: ANALYSIS OF JUDGE'S DECISION AGAINST CRIMINAL ACTIONS - Basri, Muhammad Reskiawan; Hamid, Abd. Haris; Zubaidah, Siti (Faculty Of Law Bosowa University, 2022)
This research aims to find out: Whether the criminal conviction in the verdict number 1812 / Pid.B / 2019/ PN.Mks has been in accordance with the value of public justice and how the judge's consideration in sentencing criminal convictions in verdict number 1812 / Pid.B / 2019 / PN.Mks. This research method is an qualitative normative research method. The types of data used are premier data and secondary data. Data collection techniques conduct interviews with The Judge of the State Court Class IA Makassar, and the Prosecutor of the Makassar State Prosecutor and conduct a literature of legal references related to the case. The results of this study show that the values of justice in the verdict No. 1812 / Pid.B / 2019 / Pn. have not reflected a sense of justice for victims. Ideally the Public Prosecutor and the Panel of Judges should also consider the provisions of the other articles, so that the verdict received by the accused is very likely to be more severe. Although the main provision is detention, but before committing the crime of detention, the accused is directly involved in the theft of goods from the same victim. The judge's legal consideration in imposing a criminal light weight on the perpetrator in the case of penal in the case of detention in the verdict Number: 1812 / Pid.B / 2019 / PN.Mks has considered juridically, sociologically, philosophically and also subjectively. However, in that case the judge has not considered the crime of theft committed by the defendant before committing the crime of detention, the defendant's actions have been detrimental to the victim and also the community who are restless about the behavior of theft and exposure. If this becomes a consideration that can be incriminating for the defendant, it does not rule out the possibility of imprisonment for the accused can be more than 8 (eight) months in prison.